Residual cholesterol is independently associated with arteriogenic erectile dysfunction: results from a multi-institutional study - Mei, Yangyang; Liu, Yu; Zhang, Guoyang; Chen, Yiming; Xia, Wei; Zhang, Mingran; Xu, Renfang; Zhang, Wei; Feng, Xingliang; Zhuang, Qianfeng (Frontiers in Endocrinology, 2026)
BackgroundErectile dysfunction (ED) is increasingly recognized as an early indicator of vascular health, with arteriogenic ED (AED) being the subtype most closely linked to endothelial dysfunction and atherosclerosis. Residual cholesterol (RC), a lipid fraction carried by triglyceride-rich lipoprotein remnants, has emerged as a novel marker of residual cardiovascular and metabolic risk. However, its relationship with ED, particularly AED, has not been well characterized.MethodsFrom April 2023 to May 2025, men presenting with ED and controls were consecutively recruited from three hospitals. Erectile function was assessed using the International Index of Erectile Function-5 (IIEF-5), nocturnal penile tumescence and rigidity (NPTR), and color duplex Doppler ultrasonography (CDDU) to identify AED. Demographic, lifestyle, clinical, and biochemical data were collected. RC values were calculated using the formula: RC = total cholesterol (TC) – HDL-C – LDL-C. Logistic regression and ROC curve analyses were performed to evaluate the association and predictive value of lipid parameters for AED. Logistic regression analyses were performed to evaluate associations between lipid parameters and ED/AED, adjusting for potential confounders.ResultsA total of 216 men with ED and 110 controls were included, among whom 118 were diagnosed with AED. RC levels were significantly higher in the ED group than in controls (0.57 ± 0.33 vs. 0.50 ± 0.18 mmol/L, P = 0.042), although the association with overall ED was attenuated in multivariable analysis (OR 1.086, 95% CI 0.997–1.182, P = 0.058). By contrast, RC remained robustly associated with AED after adjustment for age, BMI, smoking, CVD, TG, and TT (OR 1.471, 95% CI 1.275-1.697, P <0.001). In ROC analysis, RC showed the best predictive performance for AED (AUC 0.726, 95% CI 0.661–0.791), compared with TC (AUC 0.625, 95% CI 0.551–0.699) and TG (AUC 0.581, 95% CI 0.507–0.656). The optimal RC cutoff of 0.595 mmol/L yielded a sensitivity of 61.9% and specificity of 74.5%.ConclusionsRC was independently associated with AED and demonstrated stronger predictive ability than conventional lipid parameters. These findings suggest RC may serve as a useful biomarker for vascular risk stratification in men with ED, although prospective studies are warranted to validate these associations.